Mitigating the cognitive load of South African Sign Language interpreters on national television - Du Toit, P.T Petri (My University, 2017)
Simultaneous interpreting is inherently difficult (Gile 2009): listening to the source language and producing a target language message at the same time is a strenuous cognitive process. The cognitive load experienced by simultaneous interpreters in media settings is therefore arguably much higher than that of interpreters in conference settings (Kurz 2003). Interpreters assigned to live newscasts are exposed to a number of internal and external strains such as text complexity, rapidly changing sequences of topics and world events, and have limited time to adapt to individual speakers’ styles and a variety of accents (Kurz 2003). As the source text is read from an autocue, it is delivered at a fast, unnatural pace, which means that the simultaneous signed language television interpreter is not only faced with the threat of possible technical faults that might occur, but also the psycho-emotional strain of interpreting in front of thousands of viewers without any immediate audience response and cues. When demand outweighs the cognitive control capacity interpreters have, they may reach saturation levels (Gile 2009), and cognitive overload may occur. Cognitive overload is a major source of occupational stress (Dean and Pollard 2001) and may often cause the target audience to experience a transliterated, one-dimensional and/or superficial source text level interpretation that does not meet their expectations (Riccardi 2005). How can expert simultaneous interpreters better manage their cognitive resources while exposed to internal and external interferences? This study reports on the specific strategies used by professional South African Sign Language interpreters on national television to mitigate their cognitive load, deliver a target discourse that meets expectancy norms and thereby enhance the quality of language transfer on national television. A grounded theory approach allows for the documenting of initial norms, production and expectancy norms, as data is analysed against theoretical knowledge of simultaneous interpreting from a cognitive perspective. The study emphasises the need for South African Sign Language television interpreters to receive formal training in preparation strategies. Testing the success of a preparation model/tool and training curriculum falls outside the scope of this study, but the study opens the door to further investigation and review.
Keywords: Interpreters for the deaf--South Africa; Interpreters for the deaf--Study and teaching--South Africa; Sign language--Study and teaching--South Africa; Translating and interpreting--South Africa